Structure of ultrathin Fe films on Cu(100) prepared by pulsed laser deposition - Weinelt, Martin; Schwarz, Sergej; Baier, Holger; Müller, Stefan; Hammer, Lutz; Heinz, Klaus; Fauster, Thomas (Physical Review B, 2001)
The structures of ultrathin Fe films on Cu(100) prepared by pulsed laser deposition (PLD) and conventional thermal deposition (TD) are compared by means of low-energy electron diffraction (LEED). Below 5 ML coverage, PLD films exhibit up to four times higher integer-order LEED spot intensities, i.e., improved film quality, and show small but significant structural changes as compared to TD films. A quantitative tensor LEED analysis of the 4-ML PLD film reveals a similar 5 X 1 superstructure to that found previously for TD films, but with an enhanced surface buckling and a flat Cu bulklike iron interface layer. The latter is attributed to the incorporation of Cu atoms in the Fe interface caused by sputter effects in PLD. Above 6-ML coverage, both deposition methods yield comparable LEED I(E) spectra, revealing similar sum-face structures. The proposed structural models allow a consistent interpretation of the strongly altered magnetic properties observed for PLD-grown iron films.